A Simple Stress Test on Indonesian Islamic Banking Industry - Dece Kurniadi; Abdul Mongid; Sutan Emir Hidayat (Jurnal Keuangan dan Perbankan, 2018)
The purpose of this study is to conduct a stress test on Indonesian Islamic Banking industry in order to assess the capability of the industry to absorb the extreme risks that may happen in the future. Using data from April 2008 to September 2014, the study employs a balance sheet approach in performing the stress test on profitability and capital position and the value at risk technique for liquidity stress test. The results of this study show that in term of profitability, Islamic banks in Indonesia are immune from losses if the default rate (Non-Performing Loan) is less than 8.5 %. If the industry can improve the profit margin, the resistance will be higher. In term of capital position, by assuming loss given default (LGD) is constant at 40%, the industry will not go bankrupt if a probability of default (PD) is less than 9%. If the PD is more than 9%, a total expected loss is more than available capital. Using the value at risk (VaR) at 99% confidence, the study finds that possible deposit flight will not exceed IDR 26 trillion and the liquid asset available is IDR 28 trillion. The study concludes that there is no liquidity threat for Islamic banks in Indonesia. The finding also uncovers the risky condition that even though the capital adequacy ratio (CAR) is on average 14%, real capital measured by Equity to the total asset (ETA) is only 5.4%.JEL Classification: G17; G21DOI: https://doi.org/10.26905/jkdp.v22i1.571